Defendendo a civilização e a pátria contra o injusto agressor: as representações dos bugres e colonos nos escritos de Fidélis Dalcin Barbosa (1961-1977) - Pastre, Nathan Ferrari (2016)
This research aims to understand the representations of the figure of the "bugre" in literary writings by Fidelis Dalcin Aloe. Given the historical conflicts between Indians and European immigrants, who follow with their descendants to the present, representations of both groups were made during the process. The derogatory image of the indigenous was built in these conflicts and is revealed in different places and occasions. For this Master paper, it was chosen to analyze literary works, published in the period between 1961 and 1977, looking for understanding such representations. It was made an analysis of the process of occupation of the forested valleys of Rio Grande do Sul and Santa Catarina, as well as an analysis contacts between immigrants and indigenous and representations that emerged from these contacts. The literary works were analyzed and interpreted, understanding the sentence , the word games, the said and not said and implied, so that one could understand the representations that are made about indians. The author was born and lived in areas of Italian colonization, which were themes of his writings. The Indians often are antagonists and various works which the author writes usually has as the protagonists Italian or their descendants. While Capuchin religious, works are also imbued with a Christian morality and an ideal Christian society. The indigenous, culturally divergent immigrant often had violent contact with that, which came to occupy their land. In response, the immigrants reacted with the same violence. These contacts are recurrent theme in Barbosa’s Works. Finally, it was found that due to the period studied to be a reduction of time of indigenous reserves and territorial expansion of the descendants of immigrants, it was given that the author had lived in a region where this context was very present, constant representations in the works end denoting identities, both settlers and indigenous, to endorse the position of the settlers in the settlement process. The immigrant or descendant is seen as the bearer of progress and civilization, while the indigenous is seen as being violent and primitive. These representations are a reflection of the time in which the works were written.